2017
DOI: 10.3389/fonc.2017.00053
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hashimoto’s Thyroiditis and Thyroid Cancer in 64,628 Patients

Abstract: BackgroundThe incidence of thyroid cancer (TC) is increasing although explanatory causes are lacking. A link between cancer and inflammation is well documented but unclear for autoimmune thyroid diseases and TC. We aimed to systematically review the association between Hashimoto’s thyroiditis (HT) and papillary, follicular, medullary, anaplastic thyroid carcinoma, and thyroid lymphoma (TL).MethodsPubMed, OVID Medline, Google Scholar, and the Cochrane Library were searched from 1955 to 2016. The inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 73 publications
(58 reference statements)
7
79
0
2
Order By: Relevance
“…A relationship between the increased number of TAM and decreased survival was also reported in thyroid cancer patients . In addition, epidemiological data showed that the incidence of thyroid cancer is enhanced in chronic inflammations and in autoimmune thyroid diseases, such as Hashimoto's thyroiditis (HT) . Interestingly, Rebuffat and colleagues reported loss of epithelium integrity and a significant reduction of Tight Junctions expression (ZO‐1, Claudin, and JAM‐A) in thyroid cells from patients affected by HT .…”
Section: Discussionmentioning
confidence: 90%
“…A relationship between the increased number of TAM and decreased survival was also reported in thyroid cancer patients . In addition, epidemiological data showed that the incidence of thyroid cancer is enhanced in chronic inflammations and in autoimmune thyroid diseases, such as Hashimoto's thyroiditis (HT) . Interestingly, Rebuffat and colleagues reported loss of epithelium integrity and a significant reduction of Tight Junctions expression (ZO‐1, Claudin, and JAM‐A) in thyroid cells from patients affected by HT .…”
Section: Discussionmentioning
confidence: 90%
“…Leni et al reported that one‐third of PTC cases (33.3%, 168/505) have CLT coexistence. No association has been found between CLT and follicular, medullary, or anaplastic thyroid cancer . The coexistence of PTC and CLT is reportedly associated with better prognoses, lower rates of lymph node and distant metastases, and recurrence, particularly in patients aged ≥45 years .…”
Section: Introductionmentioning
confidence: 97%
“…HT co‐exists with papillary thyroid carcinoma, follicular adenoma, and lymphoma . The rate of occurrence of an associated carcinoma with HT in various studies has been shown up to 13% .…”
Section: Discussionmentioning
confidence: 99%
“…Fine‐needle aspiration cytology (FNAC) is a preliminary test to diagnose thyroid lesions. Association of Hashimoto's thyroiditis (HT) with follicular adenoma, papillary thyroid carcinoma, and primary thyroid lymphomas has been well described . Among the rest of malignancies, medullary thyroid carcinoma (MTC) has been least reported in the background of existing HT .…”
Section: Introductionmentioning
confidence: 99%